THE FAILURE OF INTERNAL GOVERNANCE: BOARD PROPERTIES AND EARNINGS INFORMATIVENESS IN INDONESIA - Muhammad Agung Prabowo (Akademi Akuntansi YKPN Yogyakarta, 2014)
I test the relationship between board properties and earnings informativeness in Indonesian setting. The limited attention from governance research on this issue motivates the study. The underlying conceptual framework and empirical prediction regarding the impact of properties on informativeness hinges upon agency theory. Using a sample of Indonesian listed companies, I predict that education background of directors affect discretionary accruals and earnings response coefficient. However, the study fails to provide empirical confirmation to the prediction. The background is insignificantly related to earnings informativeness and that results are robust across measure. I suspect that the results are driven by the lack of institusional development. Yet, given the shortcoming of the paper, a due care is required in interpreting the findings. Keywords: board properties, earnings informativeness, agency theory